Glacial Erosion Liberates Lithologic Energy Sources for Microbes and Acidity for Chemical Weathering Beneath Glaciers and Ice Sheets - Macdonald, Moya L.; Wadham, Jemma L.; Telling, Jon; Skidmore, Mark L. (Frontiers in Earth Science, 2018)
Wet-based regions of glaciers and ice sheets are now recognised to host unique and diverse microbial communities capable of influencing global biogeochemical cycles. However, the isolated nature of subglacial environments poses limitations upon the supply of protons for chemical weathering and energy sources (electron donors/acceptors) to support in situ microbial communities. A less well recognised source of these substrates is the release of gases from mineral structures, pore spaces or fluid inclusions and the generation of gases from the breakage of mineral bonds during the mechanical breakdown of rocks by moving ice. Here, we investigate the potential release of H2, CO2, CO and short chain hydrocarbons, particularly CH4, by glacial erosion at rates relevant to chemical weathering and microbial activity beneath glaciers. A wide range of magmatic, metamorphic and sedimentary rocks and subglacial sediments from glaciated catchments in Greenland, Norway and Canada were ground in the laboratory to varying grain sizes and the release of gases was measured. The volume of gas released increased as the grain size of the ground sediments decreased. The results of these laboratory experiments were used to estimate rates of catchment-scale gas release based upon estimates of long term abrasion rates at each glacier. H2 generation was calculated to be sufficient to potentially support previously estimated rates of methanogenesis in the upper centimetres of subglacial sediment at a gneissic catchment in Greenland and a sedimentary catchment in Canada. Sufficient CO2 could be released by grinding to drive as much as 20% of subglacial chemical weathering at a metamorphic catchment in Svalbard, with potential implications for the inferred quantity of CO2 drawn-down from the atmosphere by glacial weathering. Rates of CH4 generation from grinding bedrock has the potential to be greater than subglacial microbial generation in a sedimentary catchment in Canada with carbon rich bedrock, suggesting a potentially important source of CH4 for methanotrophic microorganisms. We conclude that mechanical erosion beneath a range of glaciers generates significant quantities of gases which have the potential to enhance chemical weathering and/or support subglacial microbial communities in the deep icy biosphere.